2009
DOI: 10.1038/oby.2009.51
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Exercise and Its Effects on Body Composition Depend on Genetic Selection History

Abstract: Little is known about how genetic variation affects the capacity for exercise to change body composition. We examined the extent to which voluntary exercise alters body composition in several lines of selectively bred mice compared to controls. Lines studied included high runner (HR) (selected for high wheel running), M16 (selected for rapid weight gain), Institute of Cancer Research (ICR) (randomly bred as control for M16), M16i (an inbred line derived from M16), HE (selected for high percentage of body fat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Results to date make it clear that the effects of physical activity on the human body mass index (BMI) vary with genotype , and similar results have been observed for different strains of mice (Nehrenberg et al, 2009a;Meek et al, 2010 For a review of the measurement of physical activity in humans, see Westerterp (Westerterp, 2009). Note that both voluntary exercise and spontaneous activity can be quantified in terms of duration, intensity or total activity (product of duration and intensity).…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 83%
See 2 more Smart Citations
“…Results to date make it clear that the effects of physical activity on the human body mass index (BMI) vary with genotype , and similar results have been observed for different strains of mice (Nehrenberg et al, 2009a;Meek et al, 2010 For a review of the measurement of physical activity in humans, see Westerterp (Westerterp, 2009). Note that both voluntary exercise and spontaneous activity can be quantified in terms of duration, intensity or total activity (product of duration and intensity).…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 83%
“…Further, the increase in endurance by lines of mice bred for high voluntary wheel running (Meek et al, 2009) and the divergence in wheel running of two rat lines bred for high or low endurance capacity indicate that exercise propensity and ability are positively genetically correlated in these rodents. [Based on mouse selection experiments, Nehrenberg et al have suggested that physical activity and body composition are negatively genetically correlated (Nehrenberg et al, 2009a).] Finally, these same lines show parallel differences in SPA, body size, percent body fat and circulating leptin levels when housed without wheels (Girard et al, 2007;Malisch et al, 2009;Meek et al, 2010;Novak et al, 2009;Novak et al, 2010) (T.G., H.S., M.A.C., T.H.M., L.E.C., W.A.…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also found that HR mice have less body fat than C mice, and even a lower % body fat than mice from a separate experiment that selectively bred for low body fat. 23 Reanalysis of mice from generation 14 (data from Houle-Leroy et al 24 ) indicates HR males have elevated carnitine palmitoyltransferase levels compared to C lines, suggesting a higher ability to oxidize fats. 9 Therefore, we hypothesized that insufficient dietary lipids may be one factor limiting further evolutionary increases in wheel running by the HR lines.…”
Section: Introductionmentioning
confidence: 99%
“…[Interestingly, HR mice also exhibit elevated home-cage activity when housed without access to running wheels (Malisch et al, 2008;Malisch et al, 2009)]. Instead, the reduced body fat (Swallow et al, 2001;Nehrenberg et al, 2009), reduced circulating leptin levels (Girard et al, 2007) (but see Vaanholt et al, 2008) and increased circulating adiponectin levels [(Vaanholt et al, 2007b) depending on sex and diet (Vaanholt et al, 2008)], suggest that lipid availability may be a limiting factor (see also Gomes et al, 2009). However, recent work in human 'ultraendurance' athletes (Pearson, 2006) suggests that neurobiological attributes make a greater contribution to performance than has previously been acknowledged (Kayser, 2003;Baden et al, 2005;Noakes, 2007;Rose and Parfitt, 2007;Noakes, 2009) …”
mentioning
confidence: 99%